Perkembangan Islam dan Praktek Islam dalam Selebaran Film Indonesia di Era Soeharto (1966-1998) - Christopher A Woodrich (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2017)
Using a corpus of 300 film flyers issued between 1966 and 1998, this article examines how Islam was depicted in advertisements for Indonesian films under the Suharto government. It finds that, although explicit symbols of Islamic religiosity were generally not included in film flyers, such depictions could still be found, both in flyers for films intended to preach Islamic values as well as in flyers for films with more general themes. Markers of Islam identified include turbans, skullcaps, headscarves, language, the Qur'an, prayers, prayer beads, mosques, and the Kaaba, all of which were used to portray an Islamic identity that was in some ways highly normative while in other ways quite diverse. Though these flyers tempered the exclusivity of Islamic identity, they are also indicative of the religion's special position in contemporary Indonesian popular discourse. The use of these markers, thus, underscores the dynamicity and fluidity of discourse on Islamic identity in Suharto-era Indonesia and emphasizes the need to recognize the contributions of popular culture to national discourse of identity, religious or otherwise.